2003
DOI: 10.1080/01926230309725
|View full text |Cite
|
Sign up to set email alerts
|

Murine Lethal Toxic Shock Caused by Intranasal Administration of Staphylococcal Enterotoxin B

Abstract: Currently available murine staphylococcal enterotoxin B (SEB) shock models require pretreatment with various agents to increase mouse sensitivity to SEB. This study was performed to show that C3H/HeJ mice are highly susceptible to intranasal SEB inoculation, which caused toxic shock without using pretreatment agents. For this purpose, mice were injected intranasally with different doses of SEB and observed for up to 1 month. The median lethal dose of SEB was determined using the probit procedure. Tissue sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These two relatively small SEB challenges trigger intense inflammation in the lung and systemic cytokine release that culminate in death more than 3 days after the initial exposure. Importantly, cytokine release, pathological lesions, and time to lethality in C3H/HeJ mice resemble findings in primate studies [30], [33], [34], [35] and clinical staphylococcal toxic shock syndrome in patients [1]. Furthermore, respiratory system challenge with the induction of a pulmonary inflammatory response simulates the manner in which SEB would be used as a bioweapon [15].…”
Section: Introductionmentioning
confidence: 64%
“…These two relatively small SEB challenges trigger intense inflammation in the lung and systemic cytokine release that culminate in death more than 3 days after the initial exposure. Importantly, cytokine release, pathological lesions, and time to lethality in C3H/HeJ mice resemble findings in primate studies [30], [33], [34], [35] and clinical staphylococcal toxic shock syndrome in patients [1]. Furthermore, respiratory system challenge with the induction of a pulmonary inflammatory response simulates the manner in which SEB would be used as a bioweapon [15].…”
Section: Introductionmentioning
confidence: 64%
“…taphylococcal enterotoxin B (SEB), a superantigen produced by Staphylococcus aureus, has deleterious effects in humans, such as food poisoning (1) and toxic shock (2). Because it can be easily aerosolized, SEB is classified as a category B agent by the Centers for Disease Control and Prevention (3).…”
mentioning
confidence: 99%
“…A high IN dose of SEB was reported to be lethal in C3H/HeJ, a TLR4-defective mouse strain, but the mechanism of intoxication was unclear [108]. A recent study revealed that this dose of SEB was ineffective in mediating SEB-induced shock, although two low doses of SEB, at least one dose must be delivered by IN, were lethal [79].…”
Section: Animal Modelsmentioning
confidence: 99%